A SEMANTIC ANALYSIS OF FIGURATIVE LANGUAGE FOUND IN EMINEM’S SONG - L.P. Karina Febriyanti Aryawan; I.W. Suarnajaya; I.W. Swandana (Lingua Scientia, 2019)
There are two functions of language, namely commucative and expressive. As people listen to the music through its lyrics, language tends to be expressive since it is able to convey the meaning and background of the song. Figurative language is used to create a special effect ot the audiences. Figurative language carries non-literal meaning which helps the songwriters to convey the meaning of their songs.  Therefore, this study aimed at identifying and describing the type and the meanings of figurative language which were used in Eminem’s song lyrics and determining the dominant type of figurative language used in the songs lyrics. This research used descriptive qualitative as the method. In collecting the data, the researcher used library research (reading and noting), since the data were already existed in the form of documentation (song lyrics). After the data were collected, the data were analyzed by using Cresswell’s theory. From the analysis, the researcher found that there are 136 data containing figurative language and 12 types of figurative language which are used in the song lyrics. Simile type of figurative language is mostly used in the song lyrics. Therefore, it is suggested that the students keep learning to do figurative language analysis in literary works in order to enrich their insight about figure of speech.